31P NMR Method for Phospholipid Analysis in Krill Oil: Proficiency Testing—A Step toward Becoming an Official Method. (24th October 2018) - Zailer, Elina; Monakhova, Yulia B.; Diehl, Bernd W. K.
Abstract: A high‐resolution 31 P NMR method for determining the concentration of phospholipid (PL) species in krill oil was proficiency tested using an international interlaboratory study. Fourteen laboratories from five countries tested five different krill oil samples providing 17 datasets. Krill oil samples were prepared by the organizer using liquid–liquid extraction and sent to the participants who ran the nuclear magnetic resonance (NMR) analysis and evaluated the spectra. The relative standard deviation (RSD) among all the results provided by the participants varied between 2.1% and 3.3% for the phosphatidylcholine (PtdCho) content and between 2.8% and 12.3% for the sum of other PL. Afterward, an automated procedure was applied to all collected NMR data, which significantly improved the RSD values and provided reliable quantitative results for specific PL (PtdCho, 1‐lysophosphatidylcholine [LPC], 2‐LPS, PtdEtn, acylphosphatidylethanolamine [APE], and lysophosphatidylethanolamine [LPE]). The RSD varied between 1.6% and 2.7% for PtdCho and between 1.6% and 2.9% for the total phosphorus. Higher but acceptable values were obtained for 1‐LPC (5.1% to 8.9%), PtdEtn (7.0% to 10.5%), and LPE (5.7% to 16.5%) due to their small concentrations. The influence of different magnetic field strengths (400–600 MHz), probes, and slight differences in acquisition parameters was assessed as nonsignificant. PtdCho hydrolysis during 14 weeks before measurements was the major factor that affects the result distribution. This method was submitted to the AOCS to become an official AOCS method for krill oil analysis.